Contemporary parking policy, practice, and outcomes in three large Australian cities. (November 2021) - Kimpton, Anthony; Pojani, Dorina; Ryan, Connor; Ouyang, Lisha; Sipe, Neil; Corcoran, Jonathan
Highlights: Develops an urban mobility conceptual framework to identify and contrast planning approaches at the major metropolitan scale. Contrasts three Australian major metropolitans by land use and transportation policy, development applications, and parking demand, supply, and price. Demonstrates that comprehensive parking data collection can identify surplus parking, and enable policy calibration and adaptive reuse. Employs spatial models to explain why and where active and more sustainable transport modal choices are chosen throughout three Australian cities. Demonstrates that metropolitan level coordination of land use and transport policy is essential and provides key recommendations. Abstract: Together, globalisation and urbanisation are accelerating the densification of cities while disruptive technologies such as micro-mobility and ride-hailing are transforming urban mobility. Amidst this change, urban planning officials and practitioners typically remain constrained to the same urban footprint, left to grapple with earlier car-oriented development, and yet must accommodate a growing population and variety of travel modes operating within the same space. Further, they must operate alongside government officials whose re-election could depend upon appeasing suburban residents that are unable or unwilling to relocate along active transport corridors, near public transit nodes, or forgo the flexibility and comfort of private automobiles. As a result, private automobiles can become necessary for traversing urban forms already enlarged by parking, driveways, roads, highways, and flyovers. Likewise, alternatives such as public and active transport can become impractical and dangerous within urban forms that are fragmented by congestion or fast traffic. Given that urban mobility research typically focuses on keeping our pre-existing modal choices moving rather than the side-effects, daily commutes have remained unchanged for decades, and planners are better equipped to continually accommodate rather than influence our modal choices. This volume of Progress in Planning aims to strengthen the evidence base for influencing modal choice by developing a comparative framework of urban mobility, and by examining how parking policy has influenced modal choice within the three largest Australian cities: Brisbane, Sydney, and Melbourne. In addition, it provides reproducible methods for estimating parking supply using land use audits, parking demand using a population census, and geo-statistical modelling for determining whether and where parking policy can explain more sustainable modal choices. As such, this volume sets a research agenda for metropolitan-scale examination and coordination of transport and land use planning for sustainable rather than temporary urban mobility.